Unravelling the Key Drivers of Soil Organic Carbon (SOC) Dynamics: A Comprehensive Review and Meta-Analysis - Pratap Dey,; Anirban Baitalik, (Journal of the Indian Society of Soil Science, 2026)
Soil organic carbon (SOC) is a vital component of soil and plays a dynamic role in the soil ecosystem, including soil health, agriculture, and climate change. Despite extensive regional-level studies on individual drivers, research lacks an integrated cause-and-effect relationship and identification of universal patterns. This review aims to prepare a relationship model of SOC drivers, depth-dependent variability, and management techniques. For this review, 2100 articles were identified using Google Scholar and ScienceDirect. After screening, 110 papers were selected for detailed review. Furthermore, to examine SOC variability in different ecosystems, data on SOC depth profiles were collected from previous studies and analysed using SPSS and Microsoft Excel. The results show that SOC maintains a positive relationship with rainfall, clay content, soil management, and organic farming, and a negative relationship with temperature, intensive agriculture, erosion, and soil pH. Meta-analysis reveals SOC decreases with depth, and grasslands contain higher SOC followed by forests and croplands. Collectively, the review suggests a need for better strategies and approaches to maintain soil health, increase food security, and address climate challenges.